Comparative transcriptomics of high-altitude Vulpes and their low-altitude relatives - Lyu, Tianshu; Yang, Xiufeng; Zhao, Chao; Wang, Lidong; Zhou, Shengyang; Shi, Lupeng; Dong, Yuehuan; Dou, Huashan; Zhang, Honghai (Frontiers in Ecology and Evolution, 2022)
The harsh environment of Qinghai-Tibet Plateau (QTP) imposes strong selective stresses (e.g., hypoxia, high UV-radiation, and extreme temperature) to the native species, which have driven striking phenotypic and genetic adaptations. Although the mechanisms of high-altitude adaptation have been explored for many plateau species, how the phylogenetic background contributes to genetic adaption to high-altitude of Vulpes is largely unknown. In this study, we generated transcriptomic data across multiple tissues of two high-altitude Vulpes (Vulpes vulpes montana and Vulpes ferrilata) and their low-altitude relatives (Vulpes corsac and Vulpes lagopus) to search the genetic and gene expression changes caused by high-altitude environment. The results indicated that the positive selection genes (PSGs) identified by both high-altitude Vulpes are related to angiogenesis, suggesting that angiogenesis may be one of the key functions of Vulpes to adapt to high-altitude environment. Besides, more PSGs associated with high-altitude adaptation were identified in V. ferrilata compared with V. v. montana, indicating that the longer the adaptation time to the high-altitude environment, the more genetic alterations of the species. Furthermore, the result of expression profiles revealed a tissue-specific pattern between Vulpes. We also observed that differential expressed genes in the high-altitude group exhibited species-specific expression patterns. In general, our research provides a valuable transcriptomic resource for further studies, and expands our understanding of high-altitude adaptation within a phylogenetic contexts.